Baseline emotional state influences on the response to animated short films: A randomized online experiment - Negrão, Juliana Gioia; Bazán, Paulo Rodrigo; de Azevedo Neto, Raymundo Machado; Lacerda, Shirley Silva; Ekman, Eve; Kozasa, Elisa Harumi (Frontiers in Psychology, 2022)
Introduction Considering the relevance of the emotional state, it is necessary to understand how daily stimuli can modulate the emotions. Animated short films are common stimuli, but it is unknown how they can modulate the emotional state. The study aimed to evaluate: how participants’ emotional state changed after watching animated short films with positive or negative emotional valence in an online experiment; the relationship between participants’ baseline score on an Emotional Intensity Scale and their potential change in the main emotion after watching the films; and the association between the initial main emotion valence and the potential change in this emotion with participants’ sociodemographic information. Methods A sample of 2,269 participants recruited during COVID-19 pandemic were randomly assigned to either watch a negative or positive animated short film. Results The results showed that, after watching a film with negative valence, participants were in a more negative emotional state than at baseline and compared with those who watched the film with positive valence. Also, individuals who had a negative baseline emotion and maintained the same emotion after the film had presented higher baseline emotional state scores (more negative emotion) than those who changed their emotions. In addition, the individuals who kept the baseline emotion had an association with age, marital status, level of education and psychiatric disorders, use of medication, and emotional awareness, while the individuals who changed the baseline emotion had an association with age, gender, and following or not social distancing recommendations. Conclusion Baseline emotional state may influence the response to animated short films and sociodemographic characteristics are associated with the initial main emotion valence and its potential change in this emotion.